Impact of single-walled carbon nanotubes on the embryo: a brief review - Al Moustafa, Ala-Eddin (Int J Nanomedicine, 2016)
Carbon nanotubes (CNTs) are considered one of the most interesting materials in the 21st century due to their unique physiochemical characteristics and applicability to various industrial products and medical applications. However, in the last few years, questions have been raised regarding the potential toxicity of CNTs to humans and the environment; it is believed that the physiochemical characteristics of these materials are key determinants of CNT interaction with living cells and hence determine their toxicity in humans and other organisms as well as their embryos. Thus, several recent studies, including ours, pointed out that CNTs have cytotoxic effects on human and animal cells, which occur via the alteration of key regulator genes of cell proliferation, apoptosis, survival, cell–cell adhesion, and angiogenesis. Meanwhile, few investigations revealed that CNTs could also be harmful to the normal development of the embryo. In this review, we will discuss the toxic role of single-walled CNTs in the embryo, which was recently explored by several groups including ours.